“Extreme Nephroptosis”: A Kidney in the Inguinal Hernia - Dmytro Shchukin; Vladyslav Demchenko; Andrii Arkatov; Roman Stetsyshyn; Gennadii Khareba; Vladyslav Bielov (Case Reports in Medicine)
We present an extremely rare case of renal ptosis from the normal orthotopic position into the cavity of inguinal hernia in a 93-year-old male patient. The following clinical case was accompanied by renal insufficiency, which was associated with the obstruction of the right ureter in the hernial sac and the stenosis of the left renal artery. The differential diagnosis between nephroptosis and dystopic kidney was based on MDCT scan images, which demonstrated the length of the right renal artery to be more than 20 cm. The patient underwent percutaneous nephrostomy through the right inguinal area and was successfully followed up for two years. We also analyzed six similar clinical cases described in the literature. This disease has, thus far, been observed exclusively in elderly men with long-standing and large inguinal hernias. The most frequent complications in these patients include ureteral strangulation in the area of the hernial gate and renal failure.